Enhancing Educational Practices through Simple Online Learning Applications for Vocational Teachers at Abdurrab Pekanbaru - Rika Melyanti; Yulanda Yulanda; Hendry Fonda (Yayasan Adra Karima Hubbi, 2025)
ABSTRACTBackground. The rapid advancement of technology in education necessitates the adoption of digital tools to facilitate effective teaching and learning processes. Purpose. The primary objective of this community service activity is to empower vocational teachers with an easy-to-use online learning platform that enhances their instructional methods and improves student engagement.Method. The application was developed using user-centered design principles to ensure it meets the specific needs of the teachers. Training sessions were conducted to familiarize the teachers with the application, followed by a pilot phase to gather feedback and make necessary adjustments. Results. The implementation of the online learning application resulted in increased teacher satisfaction, improved student participation, and a more interactive learning environment. Conclusion. The project demonstrates that simple, user-friendly digital tools can significantly enhance educational practices in vocational schools. Future community service activities should explore the long-term impacts of such applications on teaching efficacy and student outcomes.